The Extinct Law School in the Ḥadīth Canon: Retracing Legal Opinions of Isḥāq b. Rāhawayh (d. 238/853) in Sunan al-Tirmidhī - Muh Amiruddin; Muhammad Iqro Nugroho Sugiarto (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2025)
The legal school of Isḥāq b. Rāhawayh (d. 238/853) did not survive as a distinct tradition in later generations, yet it remains a significant part of early Islamic intellectual history, especially in the third century AH. Although his school disappeared, aspects of Ibn Rāhawayh’s legal thought are still preserved in works of fiqh and ḥadīth, particularly in Sunan al-Tirmidhī. This article seeks to compile and analyze his legal opinions as recorded in that work and to examine their characteristics in relation to ḥadīth and legal reasoning. Through a heuristic examination of Sunan al-Tirmidhī combined with comparative and content analysis, the study finds that most of Isḥāq b. Rāhawayh’s legal opinions are firmly grounded in ḥadīth, although some rely on weak reports. It also shows that his views display a strong textual orientation and reflect notable affinities with the legal reasoning of al-Shāfi‘ī (d. 204/820) and Aḥmad b. Ḥanbal (d. 241/855). This is evident in legal arguments that do not exhibit rigid doctrinal boundaries, but instead mirror broader patterns of juristic reasoning among scholars of his time. At the same time, his occasional reliance on weak ḥadīth and his departure from majority positions in several legal issues distinguish his thought from that of many of his contemporaries. This study thus contributes to recovering a neglected strand of early Islamic legal thought and highlights that diversity was not an anomaly, but a constitutive feature of the Islamic intellectual tradition.